Longitudinal Analysis of Silver Alginate Use for mammary wound cancer and Public Awareness - Wang Xiaoming; Fujimoko Akito; Li Mei (Indonesian Science Media, 2025)
Background: Managing chronic wounds is particularly relevant in the management of oncology patients. Silver alginate has potential in the prevention of infection and promotion of healing in chronic wounds; however, its application in mammary wound cancer is warranted for further research examination. Purpose: To assess the clinical outcomes and public perception influence on treatment uptake of silver alginate in mammary wound cancer. Methods: The longitudinal study conducted at Tianjin TEDA Hospital from January 2022 to February 2024 included a sample of 62 patients suffering from breast cancer with wound complications. Each patient received silver alginate in addition to conventional wound care. Information relating to age, wound area, infection, and exudate was documented at the start and during the follow-up visits. Dressings were applied and replenished according to clinical need. Key outcomes consisted of the level of wound repair, infection management, and clinical application with holistic guideline synthesis. A secondary criterion was societal interest through Google Trends monitoring. Findings: The data demonstrate that the use of silver alginate promoted wound healing with an increase of 45.7% in prescriptions within the study period. Furthermore, public awareness, as estimated by online searches, had a noteworthy correlation (r = 0.92, 95% CI, 0.89 – 0.95; P < .001) with prescription rates. which was significantly positive. By February 2024, wound care specialists constituted 45.6% of prescriptions, a remarkable increase from 28.3% in early 2022. Conclusions: Silver alginates have significant promise in the treatment of mammary wounds for cancer patients. There is a strong correspondence between public awareness, quantified through search data, and the adoption of silver alginate in the clinic, suggesting that more public awareness could help improve the treatment’s adoption.